Anticholesterol activity of velvet bean (Mucuna pruriensL.) towards hypercholesterolemic rats - Hana Ratnawati,; Wahyu Widowati, (Universiti Kebangsaan Malaysia, 2011)
Hypercholesterolemia is the main risk factor of atherosclerosis which is directly related to coronary heart disease. Velvet bean (Mucuna pruriens L.) is predicted to have potential anticholesterolemia since a previous study showed that this plant had high antioxidant activity. The purpose of this research was to determine the anticholesterol activity of crude extract and ethyl acetate fraction of velvet bean compared to simvastatin and vitamin E in decreasing the plasma level of total cholesterol, LDL and triglyceride and increasing the HDL level on hypercholesterolemic rats. Thirty male Wistar rats were divided into ten groups. Group I was fed with standard diet as negative control group and all the other groups were fed with high-fat diet and were given fructose solution. High-fat diet and fructose solution increased the level of total cholesterol, LDL-cholesterol and triglyceride and decreased the level of HDL-cholesterol significantly compared to the negative control group. The treatment groups were given 3 various doses of crude extract (50, 100, 200 mg/kgBW) and ethyl acetate fraction (15, 30, 60 mg/kgBW) of velvet bean, simvastatin 2.7 mg/kgBW and vitamin E 60 mg/kgBW daily for ten days. The data were analyzed by one way Analysis of Variance (ANOVA) and Duncan’s Post Hoc Test. The best results were shown by 15 mg/kgBW of ethyl acetate fraction in decreasing total cholesterol and 60 mg/kgBW of ethyl-acetate fraction for the LDL-cholesterol, 200 mg/kgBW of crude extract in increasing HDL-cholesterol and 50 and 200 mg/kgBW of crude extract and 60 mg of ethyl acetate fraction in lowering the triglyceride.